Accumulation of airborne microplastics in lichens from a landfill dumping site (Italy) - Stefano Loppi (Nature Portfolio, 2021)
Abstract The aim of this study was to assess if lichens (Flavoparmelia caperata) surrounding a landfill dumping site in Italy accumulated higher amounts of microplastics compared with lichens at more distant sites. Lichen samples were collected at three sites along a transect from the landfill: close (directly facing the landfill), intermediate (200 m), and remote (1500 m). Anthropogenic microparticles (fibres and fragments) were determined visually after wet peroxide digestion of the samples, and microplastics were identified based on a hot needle test; the type of plastic was identified by micro-Raman analysis. The results showed that lichens collected in the vicinity of the landfill accumulated the highest number of anthropogenic microfibres and fragments (147 mp/g dw), and consequently microplastics (79 mp/g dw), suggesting that the impact of landfill emissions is spatially limited. The proportion of fibres and fragments identified as microplastics was 40% across all sites and the most abundant polymer type was polyester or polyethylene terephthalate (68%). These results clearly indicated that lichens can effectively be used to monitor the deposition of microplastics.